2007
DOI: 10.1192/apt.bp.106.002725
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular monitoring with acetylcholinesterase inhibitors: a clinical protocol

Abstract: There has been significant anxiety among prescribers regarding the potential for cardiac adverse effects associated with acetylcholinesterase (AChE) inhibitors in Alzheimer's disease. There is no consensus on how to manage this cardiovascular risk, and memory clinics vary widely in their practice. Review of published evidence reveals that the incidence of cardiovascular side-effects is low, and that serious adverse events are rare. Intensive cardiovascular screening such as pre-treatment electrocardiograms or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 45 publications
(41 reference statements)
2
45
2
2
Order By: Relevance
“…Moreover, it was also reported that bradycardia, complete atrioventricular block and QT prolongation were seen in patients taking donepezil (24)(25)(26)(27)(28). Therefore, there has been significant anxiety among prescribers regarding the potential for cardiac adverse effects associated with ChEIs, such as donepezil in elderly patients with AD (29). The present results showed that donepezil therapy for each dose has no significant effect on the ECG parameters including heart rate, PR, QT and QTc interval and QRS duration in elderly patients with AD compared to the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also reported that bradycardia, complete atrioventricular block and QT prolongation were seen in patients taking donepezil (24)(25)(26)(27)(28). Therefore, there has been significant anxiety among prescribers regarding the potential for cardiac adverse effects associated with ChEIs, such as donepezil in elderly patients with AD (29). The present results showed that donepezil therapy for each dose has no significant effect on the ECG parameters including heart rate, PR, QT and QTc interval and QRS duration in elderly patients with AD compared to the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil, being a cholinesterase inhibitor, leads to increased levels of acetylcholine, which stimulates glycinergic and GABAergic inhibitory receptors by vagal neurotransmission, which in turn act to slow the heart rate (2). Th eoretically, donepezil and other acetylcholinesterase inhibitors can aggravate preexisting nodal disease and lead to AVB (2). Heart rhythm disturbances, however, are rare (3).…”
Section: Discussionmentioning
confidence: 99%
“…A heart rate check is recommended at baseline, and if the rate is <50 beats per minute, the cause of bradycardia needs to be investigated before starting the medication. Monthly follow-up is recommended after drug initiation or dosage change, and 6-month follow-up is recommended during the drug maintenance phase (2). …”
Section: Discussionmentioning
confidence: 99%
“…Safety concerns were raised in a populationbased study of a heterogeneous group of patients prescribed ChEIs for a range of dementias (with most having Alzheimer's disease) [ Although the hazard ratios were significant, the absolute number of events was small. A previously published clinical protocol suggested that pretreatment electrocardiograms and 24-hour cardiac monitoring were not justified [39], although the authors conceded that detection of bradycardia (<50 bpm) before or during treatment should be investigated further and the patient monitored more frequently thereafter.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%